2016
DOI: 10.1007/s12517-015-2200-1
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability Assessment of saltwater intrusion using simplified GAPDIT method: a case study of Azarshahr Plain Aquifer, East Azerbaijan, Iran

Abstract: The index-based method (GALDIT) has been established over the years for assessing the vulnerability of aquifers for saline water intrusion based on six parameters, i.e., groundwater occurrence, aquifer hydraulic conductivity, level of water table above the sea, distance from shore, impact of existing amplitude of saline water intrusion, and thickness of the aquifer. This method incorporates weight and the importance rating of factors to assess the vulnerable zones to saltwater. The objective of the present inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…(2021) concluded that the saltwater intrusion from the Bakhtegan Lake could threaten the groundwater resources in its coastal aquifers. Other studies also suggest the saltwater intrusion is a main contributor of groundwater degradation in different parts of Iran (e.g., Bahrami Jovein & Hosseini, 2017; Ebrahimi et al., 2016; Gorgij & Moghaddam, 2016; Noori et al., 2021; Ranjbar & Mahjouri, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…(2021) concluded that the saltwater intrusion from the Bakhtegan Lake could threaten the groundwater resources in its coastal aquifers. Other studies also suggest the saltwater intrusion is a main contributor of groundwater degradation in different parts of Iran (e.g., Bahrami Jovein & Hosseini, 2017; Ebrahimi et al., 2016; Gorgij & Moghaddam, 2016; Noori et al., 2021; Ranjbar & Mahjouri, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…To minimize the error and uncertainty of the vulnerability index, Babiker et al (2005) and Saidi et al (2011) adopted and evaluated appropriate parameters by performing two methods of sensitivity analysis, that is, the single parameter sensitivity analysis developed by Napolitano and Fabbri (1996) and the map removal sensitivity analysis developed by Lodwik et al (1990). Since the development of the theoretical weights of GALDIT parameters in 2001, the modification of ranges and weights of vulnerability parameters of the GALDIT analysis method was continuously attempted (Kazakis et al, 2018;Gorgij and Moghaddam, 2016). Among these attempts, the sensitivity analysis of the parameters helps determine the weights effectively by comparing with theoretical weights in assessing the vulnerability with the score and weight of each index (Gontara et al, 2016;Mahrez et al, 2018).…”
Section: Sensitivity Analysis For Galdit Parametersmentioning
confidence: 99%
“…Also, because of tectonics in relation to hydrogen units and groundwater flow, it is necessary to study the lithology of the formations and tectonics of the area and their role in changing water quality and groundwater movement. In terms of topography, the highest elevation is the western slopes of Sahand Mountain and the lowest points around the Lake Urmia, which have an altitude of 3100 meters and 1282 meters above sea level, respectively (Gorgij and Moghaddam, 2016).…”
Section: Geological Conditionsmentioning
confidence: 99%